Patterns of progression, treatment of progressive disease and post-progression survival in the New EPOC study - Pugh, Siân A (Br J Cancer, 2016)
BACKGROUND: The addition of cetuximab (CTX) to perioperative chemotherapy (CT) for operable colorectal liver metastases resulted in a shorter progression-free survival. Details of disease progression are described to further inform the primary study outcome. METHODS: A total of 257 KRAS wild-type patients were randomised to CT alone or CT with CTX. Data regarding sites and treatment of progressive disease were obtained for the 109 (CT n=48, CT and CTX n=61) patients with progressive disease at the cut-off date for analysis of November 2012. RESULTS: The liver was the most frequent site of progression (CT 67% (32/48); CT and CTX 66% (40/61)). A higher proportion of patients in the CT and group had multiple sites of progressive disease (CT 8%, 4/48; CT and CTX 23%, 14/61 P=0.04). Further treatment for progressive disease is known for 84 patients of whom 69 received further CT, most frequently irinotecan based. Twenty-two patients, 11 in each arm, received CTX as a further line agent. CONCLUSIONS: Both the distribution of progressive disease and further treatment are as expected for such a cohort. The pattern of disease progression seen is consistent with failure of systemic micrometastatic disease control rather than failure of local disease control following liver surgery.